Effect of low temperature and high strain rate compression on the microstructure evolution and mechanical behavior of Mg-2Y-0.6Nd-0.6Zr alloy. (December 2022) - Luo, Mei; Li, Wei; Li, Aiwen; Chen, Linbo
Mg-2Y-0.6Nd-0.6Zr alloy was implemented for compression test via split Hopkinson pressure bar under the conditions of low temperature and a high strain rate. The microstructure evolution and deformation mechanism of the processed material were characterized by optical microscopy (OM), electron backscatter diffraction (EBSD) and scanning electron microscopy (SEM) during the testing of low-temperature dynamic compression. As a result, Mg-2Y-0.6Nd-0.6Zr alloy exhibited a positive strain rate strengthening processed by low-temperature dynamic compression along the RD. In addition, the dynamic compressive strength and yield strength are significantly enhanced with the increasing strain rate, following the emerging of tension twins and a small amount of compression twins. The primary deformation mechanisms are the prismatic slip system and 101 ¯ 2 tension twins. The Mg-2Y-0.6Nd-0.6Zr was fractured in a brittle manner at low temperature.